2008
DOI: 10.2337/dc07-1622
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Arteriolar Caliber Predicts Incident Retinopathy

Abstract: Changes in retinal vascular caliber may reflect subclinical microvascular disease and provide prognostic information regarding risk of retinopathy. In this study, we examined the prospective association of retinal vascular caliber with retinopathy risk in an Australian population-based cohort. A total of 906 participants without retinopathy at baseline had retinal vascular caliber measured from photographs and were followed-up for 5 years for incident retinopathy. After adjusting for age, sex, systolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
78
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 21 publications
9
78
3
Order By: Relevance
“…Indeed, the Australian Diabetes, Obesity and Lifestyle study actually indicated retinal arteriolar dilatation as a specific and effective indicator of diabetic microvascular dysfunction that could be used as a 'pre-pathology' marker for initiation and progression in diabetic retinopathy. 65 This indicates that better-quality imaging, imaging processing, and newer techniques such as hyperspectral retinal imaging may provide tangible ways of predicting risk or monitoring progression of diabetic retinopathy in patients. We have proposed a model to explain how such alterations in retinal blood flow may lead to the initiation and progression of diabetic retinopathy (Figure 3).…”
Section: Hypoperfusion and Hyperperfusionmentioning
confidence: 99%
“…Indeed, the Australian Diabetes, Obesity and Lifestyle study actually indicated retinal arteriolar dilatation as a specific and effective indicator of diabetic microvascular dysfunction that could be used as a 'pre-pathology' marker for initiation and progression in diabetic retinopathy. 65 This indicates that better-quality imaging, imaging processing, and newer techniques such as hyperspectral retinal imaging may provide tangible ways of predicting risk or monitoring progression of diabetic retinopathy in patients. We have proposed a model to explain how such alterations in retinal blood flow may lead to the initiation and progression of diabetic retinopathy (Figure 3).…”
Section: Hypoperfusion and Hyperperfusionmentioning
confidence: 99%
“…Recent studies show that structural retinal microvascular changes, such as the presence of retinopathy or variations in retinal vascular caliber, are predictive of a range of systemic and ocular conditions, such as diabetes, stroke, coronary heart disease and heart failure, and diabetic retinopathy. [1][2][3][4][5][6][7] It has been hypothesized that dilation of retinal vessels in response to diffuse luminance flicker may reflect intrinsic endothelial function, 8 mediated possibly by nitric oxide. [9][10][11][12] Thus, such measurements may allow in vivo quantification of retinal endothelial function, which may help in understanding the physiological and pathological alterations of retinal microcirculation in various ocular and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 To date, laser coagulation remains the mainstay for therapy of diabetic retinopathy but is, for all undoubted efficacy, associated with significant ocular side effects. 2 Despite the proven effect of adequate laser therapy, recovery of visual function is rare and the demand for alternative treatment modalities is rising.…”
Section: Introductionmentioning
confidence: 99%